A cross sectional study on primary immunization coverage of children between the age group of 12-36 months under the national immunization programme in rural field practice area of Shimoga institute of medical sciences, Shimoga, Karnataka, India - Koppad, Raghavendraswamy; A., Santosh Kumar; V., Chandrashekar S.; S., Dhananjay K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Immunization is the process whereby a person is made immune or resistant to an infectious disease, typically by the administration of a vaccine. Vaccines stimulate the body’s own immune system to protect the person against subsequent infection or disease. Immunization is a proven tool for controlling and eliminating life-threatening infectious diseases and is estimated to avert between 2 and 3 million deaths each year. So it is essential to have 100% immunization coverage and to improve the knowledge of parents about vaccines and immunization. Methodology: Across-sectional study was conducted in the Ayanuru rural field practice area of SIMS, Shimoga, during the months of March 2016 for one month. Children within the age group 12-36months were included as the study subjects. 30 Cluster sampling was used. Sample size was 240 (8 clusters*30). Evaluation form given in the Universal Immunization Programme (UIP) was used as the questionnaire. Data was analyzed with the help of XL spread sheet and results are presented in proportions and percentages. Results: Among the 240 informants/guardians, all were mothers of participated children. Around 43.3% of the informant’s had studied till High school and around 10% were illiterate. Among the participants 41% were belonged to the class-IV socio-economic status. Vaccination coverage was at acceptable level for all the primary vaccines. Over all 98% of the children were fully immunized. It has been observed that 100% of coverage has been achieved for all the live vaccines (BCG, OPV, Measles) at all sub-centers of our field practice area. But in case of killed vaccine (pentavalent) coverage was less i.e. 92%. Only 23% of informants had knowledge about the BCG vaccination. When asked for the schedule of immunization, only 37.5% of the people could correctly recall. Only 20.5% of study population (parents/guardian) had knowledge about pentavalent and OPV vaccines; while half (48.5%) of the people had better awareness about measles vaccine. Conclusions: Overall, coverage of immunisation (98%) was at appreciation level in the study area. Good coverage has been established for BCG, OPV and measles. Pentavalent vaccine, the commonest vaccine missed due to lack of awareness about the disease. Even though the coverage is better awareness regarding disease covered under Universal Immunisation programme and their vaccines is very poor in the study area, which needs to be addressed soon. Coverage of pentavalent vaccine can be improved by effective community mobilization by ASHAs (Accredited Social Health activist) and using mobile phone based SMS reminders of due dates.